Optimalisasi Potensi Lokal melalui Inovasi Sabun Cuci Piring Berbasis Jeruk Nipis (Krut Nipeh) (Citrus Aurantifolia) di Desa Pasi Janeng - Girda Sepriani; Mawar A; Hilmina Itawarnemi; Mimi Mauliza; Fitriani Fitriani; Farhan Priyoga; Taufik Hidayat; Muhammad Naziri (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) of Universitas Teuku Umar for the 2025/2026 academic year, conducted in Desa Pasi Janeng, Woyla Timur Subdistrict, West Aceh Regency, focuses on the innovative use of lime (Krut nipeh) as a raw material for the production of environmentally friendly dish soap. This local resource, which has traditionally been used for domestic purposes, has not been fully exploited as a source of economic value. The program follows the POAC methodology (Planning, Organizing, Actuating, Controlling), which encompasses community outreach, soap-making workshops, hands-on production practices, and sustainability evaluations. The outcomes of this initiative include the development of an eco-friendly dish soap product, enhanced technical skills among community members, and active participation from housewives and young mothers. In the medium term, the program has succeeded in raising entrepreneurial awareness within the community, with the expectation that it will foster the establishment of micro, small, and medium enterprises (MSMEs) based on local resources, thus contributing to sustainable development. Furthermore, the program aligns with the achievement of several Sustainable Development Goals (SDGs), particularly Goals 1 (No Poverty), 8 (Decent Work and Economic Growth), and 12 (Responsible Consumption and Production), making a meaningful contribution to community service in accordance with the Tri Dharma of Higher Education.